A REGRESSION MODEL FOR THE TONS OF PRUNING PER HECTARE - Martínez-Rodríguez, Ana María; Gallego, Francisco Javier; Terrados, Julio; Castro, Eulogio (European Scientific Journal, ESJ, 2014)
More than nine million hectares of olive trees are cultivated all over the world, but especially in the Mediterranean countries. As an essential operation, pruning of olive trees produces a huge amount of biomass which is lacking of industrial applications and must be eliminated from fields to prevent propagation of vegetal diseases. This work deals with the development of a regression model to be used in the estimation of the real biomass production from olive tree pruning.